The Hemingway stories : [large type] as featured in the film by Ken Burns and Lynn Novick on PBS - Hemingway, Ernest, 1899-1961 (Thorndike Press, a part of Gale, a Cengage Company Gale, 2021)
"Ernest Hemingway, a literary icon and considered one of the greatest American writers of all time, is the subject of a major documentary by award-winning filmmakers Ken Burns and Lynn Novick. This intimate portrait of Hemingway--who brilliantly captured the complexities of the human condition in spare and profound prose, and whose work remains deeply influential in literature and culture--interweaves a close study of biographical events with excerpts from his work. The Hemingway Stories features Hemingway's most significant short stories in chronological order, so viewers of the film as well as fans old and new can follow the trajectory of his impressive life and career. Hemingway's beloved classics, such as "The Short and Happy Life of Francis Macomber," "Up in Michigan," "Indian Camp," and "The Snows of Kilimanjaro," are accompanied by fresh insights from renowned writers around the world--Mario Vargas Llosa, Edna O'Brien, Abraham Verghese, Tim O'Brien, and Mary Karr. Tobias Wolff's introduction adds a new perspective to Hemingway's work, and Wolff has selected additional stories that demonstrate Hemingway's talent and range. The power of the Ernest Hemingway's revolutionary style is perhaps most striking in his short stories, and here readers can encounter the tales that created the legend: stories of men and women in love and in war and on the hunt, stories of a lost generation born into a fractured time. This collection is a perfect introduction for a new generation of Hemingway readers and a vital volume for any fan. This book is part of the list Thorndike Press Large Print Core"--